Asymmetric Organocatalytic Stepwise [2+2] Entry to Tetra‐Substituted Heterodimeric and Homochiral Cyclobutanes. Issue 27 (24th May 2016) - Nielsen, Alex J.; Jenkins, Hilary A.; McNulty, James
Abstract: An asymmetric synthesis of tetra‐substituted cyclobutanes involving an organocatalytic, stepwise [2+2]‐cycloaddition is described. The secondary‐amine‐catalyzed method allows for the hetero‐dimerization of two different cinnamic‐acid‐derived sub‐units, opening a novel one‐step assembly to densely functionalized, head‐to‐tail coupled dimeric cyclobutanes in high enantiomeric excess. A series of selective synthetic interconversions in these sensitive cycloadducts is also described. Abstract : Head‐to‐tail approach : An asymmetric synthesis of tetra‐substituted cyclobutanes involving an organocatalytic, stepwise [2+2]‐cycloaddition is described. The secondary‐amine‐catalyzed method allows for the hetero‐dimerization of two different cinnamic acid‐derived sub‐units, opening a novel one‐step assembly to densely functionalized, head‐to‐tail coupled dimeric cyclobutanes in high enantiomeric excess. A series of selective synthetic interconversions in these sensitive cycloadducts is also described.